Hedgehogs, Squirrels, and Blackbirds as Sentinel Hosts for Active Surveillance of Borrelia miyamotoi and Borrelia burgdorferi Complex in Urban and Rural Environments - Majerová, Karolina; Hönig, Václav; Houda, Michal; Papežík, Petr; Fonville, Manoj; Sprong, Hein; Rudenko, Natalie; Golovchenko, Maryna; Černá Bolfíková, Barbora; Hulva, Pavel; Růžek, Daniel; Hofmannová, Lada; et al. (Microorganisms, 2020)
Lyme borreliosis (LB), caused by spirochetes of the Borrelia burgdorferi sensu lato (s.l.) complex, is one of the most common vector-borne zoonotic diseases in Europe. Knowledge about the enzootic circulation of Borrelia pathogens between ticks and their vertebrate hosts is epidemiologically important and enables assessment of the health risk for the human population. In our project, we focused on the following vertebrate species: European hedgehog (Erinaceus europaeus), Northern white-breasted hedgehog (E. roumanicus), Eurasian red squirrel (Sciurus vulgaris), and Common blackbird (Turdus merula). The cadavers of accidentally killed animals used in this study constitute an available source of biological material, and we have confirmed its potential for wide monitoring of B. burgdorferi s.l. presence and genospecies diversity in the urban environment. High infection rates (90% for E. erinaceus, 73% for E. roumanicus, 91% for S. vulgaris, and 68% for T. merula) were observed in all four target host species; mixed infections by several genospecies were detected on the level of individuals, as well as in particular tissue samples. These findings show the usefulness of multiple tissue sampling as tool for revealing the occurrence of several genospecies within one animal and the risk of missing particular B. burgdorferi s.l. genospecies when looking in one organ alone.
Keywords: Borrelia burgdorferi sensu lato; European hedgehog; Eurasian red squirrel; Borrelia miyamotoi; Common blackbird; Northern white-breasted hedgehog